2016
DOI: 10.21037/jtd.2016.06.06
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of coronary computed tomography angiography versus exercise electrocardiography for coronary artery disease: a systematic review and meta-analysis

Abstract: Background: Both coronary computed tomography angiography (CCTA) and exercise electrocardiography (ExECG) are non-invasive testing methods for the evaluation of coronary artery disease (CAD). However, there was controversy on the diagnostic performance of these methods due to the limited data in each single study. Therefore, we performed a meta-analysis to address these issues. Methods: We searched PubMed and Embase databases up to May 22, 2015. Two authors identified eligible studies, extracted data and acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
4
1
2
Order By: Relevance
“…With respect to our NPV, its lower result as compared to others (97%–100%)[ 11 12 ] can be explained by the difference in the sample size studied, ethnicity, and the longer follow-up period (5–8 years in our study compared to a mean of 2 years in other studies).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…With respect to our NPV, its lower result as compared to others (97%–100%)[ 11 12 ] can be explained by the difference in the sample size studied, ethnicity, and the longer follow-up period (5–8 years in our study compared to a mean of 2 years in other studies).…”
Section: Discussioncontrasting
confidence: 87%
“…This PPV goes in the same average of a wide range of PPV values present in the literature (35%–97%). [ 9 10 11 ] This relatively low PPV can be explained by the overestimation of the coronary artery narrowing detected by CCTA, secondary to blurring artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Transient coronary vasospasm is also a potential cause as suggested by a few published case reports [14][15][16]. Although CCTA has excellent negative predictive value for diagnosing CAD [17], Kang et al found poor sensitivity of CCTA for diagnosing coronary vasospasm [18]. This is another topic that requires further investigation in patients using cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, our method routinely permits very low radiation exposures (<2 mSv), low contrast volumes, and rapid imaging by free breathing without sedation. MDCT is the best non-invasive imaging technique in terms of sensibility, specifi city, positive and negative predictive value as regard this group of malformations [6]. Non-contrast Self-navigated Free-breathing MR Angiography (SN3D-MRA) studies provide considerable diagnostic accuracy regarding the detection of anomalies, high origin, and inter-arterial course of the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%